(untitled) (Islas, 2021)
El enunciado «Yo estoy aquí para contar la historia» perteneciente al poema «Amor América (1400)» de Canto General de Pablo Neruda, ha incidido en que la crítica ha puesto al centro de los abordajes el sujeto lírico nerudiano, su voz arrolladora, su verso impetuoso. Esa condición molar con que se presenta el yo, se relativiza ante la pregunta: ¿qué lugar es aquí?, pregunta que las actualizaciones del territorio Caribe permiten proponer una respuesta alejada de los espacios que la crítica ha fijado en relación a este poemario. The statement “I am here to tell the story” belonging to the poem “Amor América (1400)” from Canto General by Pablo Neruda, has influenced criticism in placing the Nerudian lyrical subject, his overwhelming voice and his impetuous verse at the center of the approaches. This molar condition with which the I presents itself is relativized when faced with the question: what place is here? A question for which the updates of the Caribbean territory allow us to propose an answer far from the spaces that the critic has set in relation to this collection of poems.